Cardiogenic shock related cardiovascular disease mortality trends in US population: Heart failure vs. acute myocardial infarction as contributing causes. (15th November 2022) - Ghajar, Alireza; Ordonez, Cesar Palacios; Philips, Binu; Pinzon, Pablo Quintero; Fleming, Lisa M.; Motiwala, Shweta R.; Sriwattanakomen, Roy; Ho, Jennifer E.; Grandin, E. Wilson; Sabe, Marwa; Garan, Arthur Reshad
Abstract: Background: Observational and trial data have revealed significant improvement in cardiogenic shock (CS) mortality due to acute myocardial infarction (AMI) after introducing early coronary revascularization. Less is known about CS mortality due to heart failure (HF), which is increasingly recognized as a distinct entity from AMI-CS. Methods and results: In this nationwide observational study, the CDC WONDER database was used to identify national trends in age-adjusted mortality rates (AAMR) due to CS (HF vs. AMI related) per 100, 000 people aged 35–84. AAMR from AMI-CS decreased significantly from 1999 to 2009 (AAPC: -6.9% [95%CI -7.7, −6.1]) then stabilized from 2009 to 2020. By contrast, HF-CS associated AAMR rose steadily from 2009 to 2020 (AAPC: 13.3% [95%CI 11.4, 15.2]). The mortality rate was almost twice as high in males compared to females in both AMI-CS and HF-CS throughout the study period. HF-CS mortality in the non-Hispanic Black population is increasing more quickly than that of the non-Hispanic White population (AAMR in 2020: 4.40 vs. 1.97 in 100, 000). The AMI-CS mortality rate has been consistently higher in rural than urban areas (30% higher in 1999 and 28% higher in 2020). Conclusions: These trends highlight the fact that HF-CS and AMI-CS represent distinct clinical entities. While mortality associated with AMI-CS has primarily declined over the last two decades, the mortality related to HF-CS has increased significantly, particularly over the last decade, and is increasing rapidly among individuals younger than 65. Accordingly, a dramatic change in the demographics of CS patients in modern intensive care units is expected. Highlights: Among US adults, AMI-CS mortality decreased substantially from 1999 to 2009 then stabilized from 2009 to 2020. Conversely, HF-CS mortality was stable from 1999 until 2009, and rose steadily from 2009 to 2020. Males had consistently higher mortality rates than females in both AMI-CS and HF-CS across all years. HF-CS mortality has been consistently higher in non-Hispanic Black individuals compared to Non-Hispanic White individuals. AMI-CS mortality has been comparable between non-Hispanic Black and White individuals.